Paternal breastfeeding self-efficacy in South Tangerang, Indonesia: a qualitative study - Sabilla, Mizna; Sartika, Ratu Ayu Dewi (Intelektual Pustaka Media Utama, 2025)
Studies focusing on paternal confidence in supporting breastfeeding remain relatively scarce, especially in Indonesia. The purpose of this study was to explore paternal breastfeeding self-efficacy among fathers in Indonesia. This study used a qualitative approach with ten participants, including fathers and mothers with children aged 6-24 months who had experience in exclusive breastfeeding. It took place in South Tangerang City between May and July 2023. Fathers participated in focus group discussions, while mothers underwent in-depth interviews. The data analysis utilized content analysis, referring to the theme of the Self-efficacy framework. This study revealed that fathers felt less confident when dealing with issues such as the baby's low weight, breastfeeding refusal, and the mother returning to work. However, seeing the consequences of not exclusively breastfeeding and the support from health workers and the community helped them stay confident. These factors, along with a sense of pride and satisfaction, strengthened their ability to support exclusive breastfeeding. Paternal breastfeeding self-efficacy is dynamic. However, previous experience, observation of others, verbal persuasion, and positive emotions strengthen fathers' beliefs. Parents need to consult a lactation counselor when facing problems while breastfeeding. Counselors can provide assistance and motivation to remain confident and continue to exclusively breastfeed.